2022
DOI: 10.1021/acs.jafc.2c00140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Pressure Processing (HPP) on Phenolics of North Atlantic Sea Cucumber (Cucumaria frondosa)

Abstract: Sea cucumber contains a wide range of bioactive compounds, including phenolics. This study investigated the free, esterified, and insoluble-bound phenolics of sea cucumber body wall as affected by high-pressure processing (HPP) pretreatment. Sea cucumber body wall was subjected to HPP (200, 400, and 600 MPa for 5, 10, and 15 min), followed by the extraction of phenolics. The contents of total phenolics and antioxidant activity were monitored. Compared to untreated samples, those treated with HPP exhibited sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The Maillard reaction involves a series of complex chemical reactions between the carbonyls of reducing sugars and proteins, mainly primary or secondary amines, which is responsible for the browning of food and its distinctive flavor [ 25 ]. The Maillard reaction develops a wide range of chemical constituents belonging to oxazole, thiophene, furan, thiazole, pyrrole, pyrazine, and pyridine, among others.…”
Section: Flavor Chemistry: Lipid Participation In Maillard Interactionmentioning
confidence: 99%
“…The Maillard reaction involves a series of complex chemical reactions between the carbonyls of reducing sugars and proteins, mainly primary or secondary amines, which is responsible for the browning of food and its distinctive flavor [ 25 ]. The Maillard reaction develops a wide range of chemical constituents belonging to oxazole, thiophene, furan, thiazole, pyrrole, pyrazine, and pyridine, among others.…”
Section: Flavor Chemistry: Lipid Participation In Maillard Interactionmentioning
confidence: 99%
“…Pre-treatments also affect the content of sea cucumber phenolic and their antioxidant activities. For example, free, esterified, and insoluble-bound phenolics from the body wall and internal organs of Atlantic sea cucumber ( Cucumaria frondosa ) were determined using high-pressure processing (HPP) pre-treatment [ 5 , 24 ]. Results demonstrated that HPP significantly improved the TPC, TFC, and antioxidant activity.…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…These phenolics demonstrated strong antioxidant activity, including DPPH radical-scavenging and metal-chelating activities. The presence of phenolics in the body wall could be due to the eating of phenolic-rich ingredients, mainly phytoplankton and particles derived from degrading marine macroalgae [ 5 ]. Likewise, phenolic compounds of Holothuria atra were identified and quantified using HPLC, and major compounds were chlorogenic acid (80.34%), pyrogallol, rutin, and coumaric acid [ 31 ].…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
See 2 more Smart Citations